UJI AKTIVITAS ANTIBAKTERI FRAKSI DARI MASERAT Zibethinus folium TERHADAP Escherichia coli - Choirul Huda; Amalia Eka Putri; Devri Windi Sari (Jurnal SainHealth, 2019)
Durian leaf (Zibethinus folium) is part of the plant that has antibacterial activity. The purpose of this study was to determine the antibacterial activity of Zibethinusfoliumfraction against Escherichia coliATCC 25922 in vitro. The research method used is experimental. Leaf samples were extracted using maceration method with 70% ethanol and purified by fractionation methods using aqua distilled, n-hexane, and ethyl acetate. Positive controlisclindamycin gel and negative controlis5% DMSO. Statistical analysis was performed with One-Way Anova. Phytochemical screening results show that macerateZibethinus folium contains flavonoids, tannins, saponins and steroids. The test results of antibacterial activity aqua distilled fraction and ethyl acetate fraction of macerateZibethinus foliumshows antibacterial activity against Escherichia coliATCC 25922, while the n-hexane fraction of macerateZibethinus foliumshowed no antibacterial activity against Escherichia coliATCC 25922. aqua distilled fraction of 40% showed a response the most well barriers with zone of inhibition 8.33 ± 0.76 mm, meaning that aqua distilled fraction of 40%  including medium category.